2014
DOI: 10.1111/cpf.12206
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of rehabilitative ultrasonographic imaging for muscle thickness measurement of the rhomboid major

Abstract: In this study, the intra- and interexaminer reliability of muscle thickness measurements of the rhomboid major were good. Therefore, we suggest that muscle thickness measurements of the rhomboid major obtained with the RUSI technique would be useful for clinical rehabilitative assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(24 reference statements)
0
9
0
3
Order By: Relevance
“…Intra-rater reliability was not evaluated in our study for a few reasons. First, because high intra-rater and test–retest reliability of US muscle thickness measurement have already been demonstrated in the trunk muscles [ 20 , 23 , 30 , 32 ] as well as in other body regions [ 33 , 34 , 35 , 36 ]. Secondly, during semi-controlled experiments prior to the study, a high consistency was observed for the repeated US measurements among the different examiners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-rater reliability was not evaluated in our study for a few reasons. First, because high intra-rater and test–retest reliability of US muscle thickness measurement have already been demonstrated in the trunk muscles [ 20 , 23 , 30 , 32 ] as well as in other body regions [ 33 , 34 , 35 , 36 ]. Secondly, during semi-controlled experiments prior to the study, a high consistency was observed for the repeated US measurements among the different examiners.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound imaging could be an easy-to-use, low-cost, and radiation-free method to determine muscle thickness [ 20 ] and to avoid or decrease the occurrence of complication during therapeutic [ 21 ] or diagnostic [ 22 ] needle procedures. In fact, several studies have proposed different ultrasound (US) imaging protocols for assessing thickness or depth evaluation of several trunk muscles, e.g., rhomboids [ 23 ], pectoralis major [ 24 ], or lower trapezius [ 25 ], and have reported moderate to excellent relative inter- and intra-rater reliability associated with appropriate measurement errors, as well as agreement with other methods as MRI [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, the intra‐ and interrater reliability of the ultrasonographers who performed the measurements was not evaluated. However, Jeong et al [18] have reported that ultrasonographic measurements of RM thickness have demonstrated good intra‐ and interrater reliability. Second, some examiner training is required to correctly identify the feeling of needles passing through the fascia covering the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…rhomboid major [14], middle [15], and lower trapezius [16]; supraspinatus [17,18]; and infraspinatus [19]. Although the reliability of RUSI measurements for several shoulder muscle thicknesses has been demonstrated, the reliability of small pectoral muscle thickness measurements by RUSI…”
Section: ⅰ Introductionmentioning
confidence: 99%